Isokinetic strength of shoulder rotator muscles in powerlifters: correlation between isometric and concentric muscle actions - Lucena, E. G.; Ferland, P. M.; Ahmadi, S.; Teixeira, L. F.; Comtois, A. S.; Uchida, M. C. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Isokinetic strength has been useful to assess muscle function related to sports and prevent injuries. The present study measured the isokinetic isometric and concentric shoulder rotators strength, agonist/antagonist ratio, and examined the relationships between isometric and concentric peak torque, and agonist/antagonist ratio in powerlifters compared to a control group. METHODS: The participants were divided into two groups: powerlifters group (N.=14) and physically active group (N.=9). Participants` were evaluated on isokinetic dynamometer for isometric, and concentric (two velocities, 60°/s and 180°/s) strength of shoulder external (ER) internal rotation (IR). Isometric contractions lasted 10 seconds, and concentric modes were 5 repetitions. RESULTS: Bilateral significant differences, between dominant and non-dominant side, were found in ER peak torque at isometric mode in powerlifters group (P=0.021). Powerlifters showed higher IR peak torque at isometric mode in dominant (P=0.040) and non-dominant side (P=0.014) than physically active group. Pearson correlations between isometric peak torque and concentric velocities ranged between 0.49 and 0.89 for powerlifters group, and between 0.73 and 0.93 for physically active group. For agonist/antagonist ratio, pearson correlation ranged between 0.47 and 0.83 for powerlifters group, and between 0.48 and 0.86 for physically active group. CONCLUSIONS: The bilateral differences in ER movement at isometric mode in powerlifters suggest that exercises for shoulder rotators must be included on training for joint safety and balance between sides despite isometric shoulder rotators strength in powerlifters was higher than physically active individuals. Results presented positive correlation between both muscle actions, isometric and concentric, in peak torque and agonist/antagonist ratio.